Avaliação de programas educacionais: estudo sobre variáveis de suporte psicossocial e material do Projeto Primeiro Passo - Nascimento, Sumara Frota do (2019)
This dissertation aims to evaluate the impacts that the First Step Project develops for young apprentices in Fortaleza / CE through material and psychosocial variables. Exploratory research based on qualitative and quantitative approaches, exploratory in nature, developed according to the proposal of Bruyne, Herman and Schouthete (1977), was a quadripolar methodological space. The epistemological pole rests on Pierre Bourdieu's epistemological foundations in the view of a sociological epistemology. The theoretical pole, as a field of concepts brings the systematics of the object under study constituting a frame of references and reflections about the theory proposed from Pierre Bourdieu's concepts as habitus, field and capital that are coherent with the understanding of the context in which it involves evaluation of educational programs and projects, as well as the highlighting of the material and psychosocial support variables. The morphological pole integrates the section of the models used in the work proposal, based on the view of theorists thus highlighted and listing the structuring of the theories and the form of application of the evaluation models, highlighting the IMPACT model and the MAIS model. The technical pole presents the details of data collection, aiming to compare it with the theory, from the methods and techniques necessary for the investigation of the object under study. The population consisted of 74 young people participating in the First Step Project as a Young Apprentice. Questionnaires (closed and open questions) were applied, corresponding to the respondents' profile, evaluation of the material and psychosocial support variables through a 20 (twenty) item evaluation scale measured by the likert scale, and qualitative evaluation of the variables regarding the project. . The resulting data in its quantitative aspect were analyzed using the Statistical Package for Social Sciences (SPSS), version 20.0 for Windows and its qualitative aspect with the aid of Computer Assisted Qualitative Data Analysis Software -CAQDAS (Altas.ti 8 ), version 8.1 in Portuguese for Windows. The results showed that the obtained scales present satisfactory psychometric indices. Regarding the characteristics of the qualitative data, the results corresponded to the specific literature. The research showed that the variables found both material and psychosocial influence the learning process of young people who participated in the project. Improvements in the development of these variables are needed for better performance of young student / intern activities contributing to a better quality of the services offered.